2022
DOI: 10.3390/biomedicines10030627
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiological Correlates of Gaze Perception in Healthy Individuals and Neurologic Patients

Abstract: The ability to adaptively follow conspecific eye movements is crucial for establishing shared attention and survival. Indeed, in humans, interacting with the gaze direction of others causes the reflexive orienting of attention and the faster object detection of the signaled spatial location. The behavioral evidence of this phenomenon is called gaze-cueing. Although this effect can be conceived as automatic and reflexive, gaze-cueing is often susceptible to context. In fact, gaze-cueing was shown to interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 161 publications
(254 reference statements)
0
35
0
Order By: Relevance
“…Significant changes were found in cerebral areas involved in the emotion and cognition functions, two mental processes that are frequently impaired in MDD. Specifically, morphological modifications were observed in the frontal and temporal lobes, the hippocampus, the thalamus, the striatum, and the amygdala [ 11 , 12 ]. Several studies focused on the ventromedial portion of the prefrontal cortex (vmPCF), considering its involvement in fear conditioning, a mechanism that is aberrant in depressive disorders [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant changes were found in cerebral areas involved in the emotion and cognition functions, two mental processes that are frequently impaired in MDD. Specifically, morphological modifications were observed in the frontal and temporal lobes, the hippocampus, the thalamus, the striatum, and the amygdala [ 11 , 12 ]. Several studies focused on the ventromedial portion of the prefrontal cortex (vmPCF), considering its involvement in fear conditioning, a mechanism that is aberrant in depressive disorders [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial symptoms in Parkinson’s disease may be depression and other non-motor manifestations, including impaired non-verbal communication and expressivity [ 63 , 64 , 65 ]. Quinolinic acid is a possible trigger for depression and other non-motor symptoms.…”
Section: Quinolinic Acidmentioning
confidence: 99%
“…Demyelination of particular structures and imbalance due to the interaction of a dysregulated immune system and specific lymphocyte receptors can lead to negative impacts such as neuropsychiatric, autonomic, cognitive, and sleep complications in MS. In this regard, research in healthy people has demonstrated that the modulation of autonomic nervous system responses is critical for behavioral regulation, showing how this function is compromised in MS patients [96,[125][126][127].…”
Section: Role Of Fatty Acids In Microglial Polarization In Msmentioning
confidence: 99%